Um estudo sobre a minimização de funcionais de expoente variável aplicados à restauração de imagens digitais - Silva, Daniel Hilário da (2009)
We studied in this work a functional with exponent variable, ie 1 ≤ p(x) ≤ 2, which provides a model for restoration of digital images, specifically for the removal of noise. The difiusion resulting of the proposed model is a combination of total variation with isotropic difiusion. The existence, uniqueness and behavior as t ! 1 from the solution of the model will be analyzed and also presented. Experimental results are presented in order to illustrate the eficiency of the model to be used to remove the noise.